Protective Effect of Peach Gum Polysaccharides on DSS-induced Ulcerative Colitis in Mice - Rui DING; Wenxiu WANG; Yuanren ZHU; Yue CAO; Min FANG; Qing YANG; Zhiyong GONG (Shipin gongye ke-ji)
Objective: To investigate the protective effect of peach gum polysaccharides (PGP) on ulcerative colitis induced by dextran sulfate sodium (DSS) in mice. Methods: Forty-eight male C57BL/6J mice were randomly divided into six groups: blank control group (KB group), peach gum polysaccharide treatment group (PGP group), model control group (M), low-dose PGP group (LP group), medium-dose PGP group (MP group), and high-dose PGP group (HP group). Except for the KB and PGP groups, mice were given 3% DSS solution to induce the colitis model in other groups. Mice in low-dose, medium-dose and high-dose PGP groups were given 200, 400 and 600 mg/kg PGP, respectively. The changes in body weight, the disease active index (DAI) score, colon tissue morphology, inflammatory factor levels, oxidative stress indices and intestinal flora were analyzed to investigate the protective effects of PGP intervention on ulcerative colitis in mice. Results: PGP administration could slow down the body weight loss of colitis mice, decrease DAI score, relieve the symptoms of colonic atrophy and colonic tissue injury. PGP highly significantly decreased the levels of pro-inflammatory factors TNF-α and IL-1β (P<0.0001). Furthermore, MPO (P<0.05) and MDA activities were reduced, and GSH and SOD levels were restored. In addition, PGP enhanced the diversity of intestinal flora, and increased the relative abundance of beneficial bacteria such as Muribaculum, Lactobacillus, Clostridium, Lachnospiraceae, while reducing the relative abundance of certain harmful bacteria such as Bacteroidaceae, Enterobacteriaceae, Tannerellaceae. These findings demonstrate that PGP could protect the intestinal homeostasis by regulating intestinal flora, inhibit the expression of inflammatory factors, and reduce colon oxidative stress, thereby reducing inflammatory response, repairing colon damage, and effectively alleviating DSS induced ulcerative colitis in mice.